2019
DOI: 10.1080/03075079.2019.1647416
|View full text |Cite
|
Sign up to set email alerts
|

How well are students engaging with the careers services at university?

Abstract: Employability is a key concern for students and it is of increasing importance to universities with the inclusion of employability outcomes affecting performance in league tables and in the Teaching 3 Excellence Framework. Universities typically teach employability either by embedding it within a 4 course curriculum (embedded approach) or via the career services (parallel approach). This article 5 explores the ratio of United Kingdom (UK) Psychology departments adopting an embedded approach vs a parallel appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 24 publications
(31 reference statements)
2
40
0
Order By: Relevance
“…Australian employers who expressed dissatisfaction regarding graduates’ employability skills for their 2014 intake suggested that some of the graduates lacked preparation for the job application and interview process, work readiness and certain technical skills needed by the recruiter, and needed to have undertaken work placements (GCA, 2016). This was borne out by responses of employees surveyed, with fewer than 45% of graduates indicating that their degree programs had prepared them well in terms of “work experience.” An examination of the literature related to work experience shows that placements, internships and other forms of well-planned, structured workplace experiences that incorporate reflection and meaningful feedback have a positive impact on the employability of students (Bradley et al, 2019; Cranmer, 2006; Jackson, 2013). This evidence, coupled with the finding that students can have low engagement with employability teaching outside of curricula (see Bradley et al, 2019), lends support to the proposal that WIL activities need to be incorporated into core curriculum activities rather than being an extra-curriculum activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Australian employers who expressed dissatisfaction regarding graduates’ employability skills for their 2014 intake suggested that some of the graduates lacked preparation for the job application and interview process, work readiness and certain technical skills needed by the recruiter, and needed to have undertaken work placements (GCA, 2016). This was borne out by responses of employees surveyed, with fewer than 45% of graduates indicating that their degree programs had prepared them well in terms of “work experience.” An examination of the literature related to work experience shows that placements, internships and other forms of well-planned, structured workplace experiences that incorporate reflection and meaningful feedback have a positive impact on the employability of students (Bradley et al, 2019; Cranmer, 2006; Jackson, 2013). This evidence, coupled with the finding that students can have low engagement with employability teaching outside of curricula (see Bradley et al, 2019), lends support to the proposal that WIL activities need to be incorporated into core curriculum activities rather than being an extra-curriculum activity.…”
Section: Discussionmentioning
confidence: 99%
“…This was borne out by responses of employees surveyed, with fewer than 45% of graduates indicating that their degree programs had prepared them well in terms of “work experience.” An examination of the literature related to work experience shows that placements, internships and other forms of well-planned, structured workplace experiences that incorporate reflection and meaningful feedback have a positive impact on the employability of students (Bradley et al, 2019; Cranmer, 2006; Jackson, 2013). This evidence, coupled with the finding that students can have low engagement with employability teaching outside of curricula (see Bradley et al, 2019), lends support to the proposal that WIL activities need to be incorporated into core curriculum activities rather than being an extra-curriculum activity. If students in the environmental sciences are to be competitive in the workplace, they will have to build up a portfolio of demonstrated experience; HEIs can facilitate this process by increasing opportunities for WIL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, very few HE institutions use tracer studies or employer surveys to find out how useful the skills that graduates acquire are to their employers. According to Bradley et al (2021), employability can be taught; therefore, it is vital to teach employability as part of the core curriculum in a degree program and review the curriculum to determine the relevance of the skills taught to labor market needs. However, universities in Tanzania have rarely reviewed their curricula to keep pace with changing job market demands and maintain the relevance of their programs.…”
Section: Regular University Curriculum Reviewsmentioning
confidence: 99%
“…The provision of a cohort-wide report and resources for educators and careers practitioners has the potential to embed employability development opportunities within the curriculum and engage career development learning (CDL) expertise which few educators possess (Holmes 2013). Integrating employability development opportunities across each year of study is also likely to reduce the proportion of students who defer CDL engagement until the final year of study (Bradley, Quigley, and Bailey 2019).…”
Section: Implications For Stakeholdersmentioning
confidence: 99%